Static disorder and structural correlations in the low temperature phase of lithium imide - Miceli, G; Ceriotti, M; Bernasconi, M; Parrinello, M (2010)
Based on ab-initio molecular dynamics simulations, we investigate the low temperature crystal structure of Li2NH which in spite of its great interest as H-storage material is still matter of debate. The dynamical simulations reveal a precise correlation in the fractional occupation of Li sites which leads average atomic positions in excellent agreement with diffraction data and solves inconsistencies of previous proposals.